At Johnmiedema.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

## Sagot :

**Answer:**

v = 6

u = 6×sqrt(2)

**Step-by-step explanation:**

since the "side angles" are the same, it is an isosceles triangle. that means both sides are equally long.

so, v = 6

for u (the baseline) we use Pythagoras :

c² = a² + b²

u² = 6² + 6² = 36 + 36 = 72

u = sqrt(72) = sqrt(36×2) = 6×sqrt(2)

**Answer:**

v = 6, u = 6[tex]\sqrt{2}[/tex]

**Step-by-step explanation:**

This is a 45- 45- 90 triangle with ratio of sides 1 : 1 : [tex]\sqrt{2}[/tex]

That is the legs are equal and the hypotenuse is [tex]\sqrt{2}[/tex] × leg

Then

v = 6 and u = 6[tex]\sqrt{2}[/tex]